Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acssuschemeng.2c07144
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Energy Storage Performance of Zr-Doped TiNb2O7 Nanospheres Prepared by the Hydrolytic Method

Abstract: The use of TiNb2O7 (TNO) as an anode material for Li-ion battery is attracting tremendous attention because of its stable structure and high theoretical capacity. However, the inherent poor electronic conductivity and ionic conductivity restrict its practical application. Herein, we designed and prepared zirconium-doped TiNb2O7 nanospheres (Zr x -TNO NSs, x = 0, 0.05, 0.010) with pores through a simple hydrolysis method to adjust the lattice spacing and electron distribution. The nanosphere-structured electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Liu et al 43 claimed that the electronic conductivity of TiNb 2 O 7 can be improved by homovalent substitution of Ti 4+ with Zr 4+ ions, but their calculations of the electronic structure and experimental measurements of the band gap did not show a significant increase in electronic conductivity. Yu et al 44 used substitution of Nb 5+ with Zr 4+ ions and demonstrated an increase in electronic and ionic conductivity of TiNb 2 O 7 . The improved rate performance of Zr 4+ -doped TiNb 2 O 7 can be explained by the increased lithium-ion conductivity due to an increase in the cell volume.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
“…Liu et al 43 claimed that the electronic conductivity of TiNb 2 O 7 can be improved by homovalent substitution of Ti 4+ with Zr 4+ ions, but their calculations of the electronic structure and experimental measurements of the band gap did not show a significant increase in electronic conductivity. Yu et al 44 used substitution of Nb 5+ with Zr 4+ ions and demonstrated an increase in electronic and ionic conductivity of TiNb 2 O 7 . The improved rate performance of Zr 4+ -doped TiNb 2 O 7 can be explained by the increased lithium-ion conductivity due to an increase in the cell volume.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
“…11 It is common knowledge that fast reaction kinetics requires high conductivity and fast Li + diffusion capability of the active materials, and inherent low ionic conductivity and sluggish Li + diffusion kinetics (E10 À15 cm 2 s À1 ) would lead to inferior fast-charging capability of the micrometer-scale bare TiNb 2 O 7 material with long charge transport distance. 12,13 Several effective approaches have been explored and lead the direction of facilitating charge transport and electrochemical reaction based on nanomaterial design, including elemental doping (e.g., Cu 2+ , Mo 6+ , V 5+ and Zr 4+ ), [14][15][16][17] composite structure construction (e.g., secondary nano-assembly and porous microsphere) [18][19][20][21] and surface engineering (e.g., carbon and Mexene coating). [22][23][24] Despite the exciting progress in achieving fast charge/discharge properties at the material level, nanostructures of the as-fabricated TiNb 2 O 7 would cause low compaction density of the electrode and serious parasitic reactions with the electrolyte due to the high accessible surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Several effective approaches have been explored and lead the direction of facilitating charge transport and electrochemical reaction based on nanomaterial design, including elemental doping ( e.g. , Cu 2+ , Mo 6+ , V 5+ and Zr 4+ ), 14–17 composite structure construction ( e.g. , secondary nano-assembly and porous microsphere) 18–21 and surface engineering ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The key is to explore materials with continuous crystal structures for excellent conductivity, open host lattices for fast Li + diffusion, and suitable lithiation potentials (41.0 V vs. Li + /Li) for adequate safety. Combined with the above requirements, titanium-based oxides (such as Li 4 Ti 5 O 12 , 8,9 TiO 2 10 ) and niobium-based oxides (such as Nb 2 O 5 , 6,11,12 Ti/Nb oxides, [13][14][15][16][17][18][19] Mo/Nb oxides, 20,21 and W/Nb 1,5,[22][23][24][25][26] ) have been considered as promising candidates for high-rate anodes at the micrometer scale. The operating voltage (1.0-2.0 V vs. Li + /Li) of these materials limits the formation of lithium dendrite and SEI film even at very high rate, simultaneously suppresses the degradation of electrolyte, which results in a good security performance.…”
Section: Introductionmentioning
confidence: 99%
“…Doping with alien ions has been demonstrated as an effective strategy to improve the electronic conductivity and Li + ion diffusion coefficient of intercalation-type electrode materials. [13][14][15][16][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] For instance, Lu's group successfully introduced Ru 4+ into micron-sized TiNb 2 O 7 powders through a solid-state reaction and the Ru 0.01 Ti 0.99 Nb 2 O 7 exhibited better cycling and rate properties than pure TiNb 2 O 7 . 15 Sun et al reported an interstitial and substitutional V 5+ -doped TiNb 2 O 7 microspheres with enhanced electronic conductivity and ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%